1977
DOI: 10.1007/bf02082669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indomethacin on renal function in anaesthetized dogs

Abstract: The inhibitory action of indomethacin administered as a single-dose injection (4mg/kg) was examined under general anaesthesia in dogs, moderate volume expansion having been induced with physiological saline infusion. At 20 to 30 min after the administration of indomethacin, excretion of Na and water showed a fall of the same extent, GFR remaining stable and the effective plasma flow (CPAH) declining. RBF estimated by the 86Rb method decreased from 411 +/- 96 ml/min/100 g to 292 +/- 53 ml/min/100 g (p less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Inhibition of PG synthesis by IM is fol lowed by a decrease in total RBF, with shifting toward the outer cortical layers both in the isolated canine kidney and in the anaesthetized-laparotomized dog [1,4,5,13,14,25]. In accordance with these findings • Outer and inner cortical blood flow per 100 g kidney.…”
Section: Discussionsupporting
confidence: 76%
“…Inhibition of PG synthesis by IM is fol lowed by a decrease in total RBF, with shifting toward the outer cortical layers both in the isolated canine kidney and in the anaesthetized-laparotomized dog [1,4,5,13,14,25]. In accordance with these findings • Outer and inner cortical blood flow per 100 g kidney.…”
Section: Discussionsupporting
confidence: 76%
“…Natriuresis has been demonstrated following renal arterial infusion of PGA and PGE [1][2][3][4][5], and this effect can be abolished by PG synthesis inhibitors [6][7][8]. In contrast, other authors observed an increased sodium excretion when PG synthesis inhibitors were administered either to conscious dogs [9], to hypophysectomized dogs [10] or to blood-perfused dog kidneys [II], These discrepan cies may be related to variations in the experimental conditions [12].…”
mentioning
confidence: 97%